Financialization, Distance and Global Food Politics - Jennifer Clapp (The Journal of Peasant Studies, 2014)
This paper provides a new perspective on the political implications of intensified financialization in the global food system. There has been a growing recognition of the role of finance in the global food system, in particular the way in which financial markets have become a mode of accumulation for large transnational agribusiness players within the current food regime. This paper highlights a further political implication of agrifood system financialization, namely how it fosters ‘distancing’ in the food system and how that distance shapes the broader context of global food politics. Specifically, the paper advances two interrelated arguments. First, a new kind of distancing has emerged within the global food system as a result of financialization that has (a) increased the number of the number and type of actors involved in global agrifood commodity chains and (b) abstracted food from its physical form into highly complex agricultural commodity derivatives. Second, this distancing has obscured the links between financial actors and food system outcomes in ways that make the political context for opposition to financialization especially challenging.